Mechanism of the formation of contractile ring in dividing cultured animal cells. I. Recruitment of preexisting actin filaments into the cleavage furrow (The Rockefeller University Press, 1990)
Cytokinesis of animal cells involves the formation of the circumferential actin filament bundle (contractile ring) along the equatorial plane. To analyze the assembly mechanism of the contractile ring, we microinjected a small amount of rhodamine-labeled phalloidin (rh-pha) or rhodamine-labeled actin (rh-actin) into dividing normal rat kidney cells. rh-pha was microinjected during prometaphase or metaphase to label actin filaments that were present at that stage. As mitosis proceeded into anaphase, the labeled filaments became associated with the cortex of the cell. During cytokinesis, rh-pha was depleted from polar regions and became highly concentrated into the equatorial region. The distribution of total actin filaments, as revealed by staining the whole cell with fluorescein phalloidin, showed a much less pronounced difference between the polar and the equatorial regions. The sites of de novo assembly of actin filaments during the formation of the contractile ring were determined by microinjecting rh-actin shortly before cytokinesis, and then extracting and fixing the cell during mid- cytokinesis. Injected rhodamine actin was only slightly concentrated in the contractile ring, as compared to the distribution of total actin filaments. Our results indicate that preexisting actin filaments, probably through movement and reorganization, are used preferentially for the formation of the contractile ring. De novo assembly of filaments, on the other hand, appears to take place preferentially outside the cleavage furrow.